Organizational Culture and Its Effect on Employee Work Discipline: Evidence From Harapan Jaya Ice Factory - Irsad Mursalaat, A. Muh. Cakra; Ruma, Zainal; Hamka, Rezky Amalia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
This study aims to investigate the influence of organizational culture on employee work discipline at Harapan Jaya Ice Factory. Organizational culture plays a vital role in shaping employees’ behavior, attitudes, and performance consistency within a company. A strong and well-communicated culture can create a shared understanding of organizational goals and expected standards, including discipline in the workplace. This research adopts a quantitative method with an explanatory approach to determine the relationship between the variables. The study involved a total population of 35 employees, all of whom were selected as the research sample through a saturated sampling technique. Data were collected using a structured questionnaire and processed using simple linear regression analysis with the support of SPSS version 25. The findings reveal that organizational culture has a positive and significant impact on employee work discipline. This means that improvements in the company’s organizational culture are directly associated with increased levels of employee discipline. Elements such as shared values, norms, communication patterns, and leadership behavior were identified as important aspects contributing to this outcome. This study contributes to the growing body of knowledge on organizational behavior by providing empirical evidence of the role of culture in enhancing employee discipline. Practically, the findings suggest that companies should strengthen their internal culture to support performance consistency and long-term organizational success.